2018
DOI: 10.1002/jclp.22649
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional beliefs towards motherhood and postpartum depressive and anxiety symptoms: Uncovering the role of experiential avoidance

Abstract: Dysfunctional motherhood-related beliefs are cognitive vulnerabilities for postpartum psychological disorders and should be assessed to identify women that may be prone to early interventions. Moreover, dysfunctional beliefs seem to affect psychopathological symptoms by activating experiential avoidance strategies (e.g., rumination), which may accentuate the frequency of women's negative thoughts and emotions. Early interventions should target the promotion of acceptance of private negative experiences (psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…First, baseline scores on self-regulatory skills and depressive symptoms were significantly associated, with women who presented poorer self-regulatory skills (more emotion regulation difficulties, high psychological inflexibility and low self-compassion) showing higher levels of depressive symptoms. These results were congruent with prior research that has suggested that poorer emotion regulation (Haga et al, 2012; Marques et al, 2018), higher psychological inflexibility (Zhu et al, 2015; Fonseca et al, 2018b) and poorer levels of self-compassion (Felder et al, 2016) may increase the likelihood of postpartum depressive symptoms. Without clinical intervention, these poorer self-regulatory skills may also contribute to the persistent nature of depressive symptoms over time, leading to the establishment of a clinical diagnosis of PPD.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…First, baseline scores on self-regulatory skills and depressive symptoms were significantly associated, with women who presented poorer self-regulatory skills (more emotion regulation difficulties, high psychological inflexibility and low self-compassion) showing higher levels of depressive symptoms. These results were congruent with prior research that has suggested that poorer emotion regulation (Haga et al, 2012; Marques et al, 2018), higher psychological inflexibility (Zhu et al, 2015; Fonseca et al, 2018b) and poorer levels of self-compassion (Felder et al, 2016) may increase the likelihood of postpartum depressive symptoms. Without clinical intervention, these poorer self-regulatory skills may also contribute to the persistent nature of depressive symptoms over time, leading to the establishment of a clinical diagnosis of PPD.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the extensive body of research on contextual (e.g., socioeconomic status, marital status, lack of social support) and clinical (e.g., prior history of depression) risk factors for PPD (Robertson et al, 2004; O’Hara and McCabe, 2013), there are some recent studies (e.g., Haga et al, 2012; Felder et al, 2016; Fonseca et al, 2018b) linking the absence of self-regulatory skills, such as emotion regulation abilities, psychological flexibility, and self-compassion, to the development and maintenance of PPD. Emotion regulation abilities may be defined as the individual’s ability to be aware of and to understand their emotional states and to use flexible and situationally appropriate strategies to address emotions and engage in goal-directed behaviors (Gratz and Roemer, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ndings are consistent with the results of previous qualitative research which have attributed unrealistic expectations of motherhood, and guilt and self-blame, to psychological di culties in the postnatal period [13,18,53]. This also ts with quantitative evidence of maladaptive beliefs towards motherhood increasing the risk of perinatal anxiety and depressive symptoms [54][55][56], and the reported relationship between dysfunctional perfectionism and postnatal distress [57]. As such, interventions to manage misconceptions around mothering ideals and better prepare women for the challenges of pregnancy and motherhood, such as infant crying and sleep deprivation, may be helpful in reducing perinatal distress.…”
Section: Sources Of Perinatal Distresssupporting
confidence: 91%
“…These ndings are consistent with the results of previous qualitative research which have attributed unrealistic expectations of motherhood, and guilt and self-blame, to psychological di culties in the postnatal period [13,18,53]. This also ts with quantitative evidence of maladaptive beliefs towards motherhood increasing the risk of perinatal anxiety and depressive symptoms [54][55][56],…”
Section: Sources Of Perinatal Distresssupporting
confidence: 91%